All hands on deck : navigating your team through crises, getting your organization unstuck, and emerging victorious - Boni, Peter J., 1945- (Career Press, 2015)
Beginning with the riveting, true story of Massachusetts clipper ship Captain Josiah Nickerson Knowles who saved his crew and all but one passenger during not one but two shipwrecks in the Pacific, author Peter J. Boni demonstrates how adversity should be embraced, rather than avoided. Boni presents a proven process to overcome chaos and disorder. The 12-Step Kedge-Off Process that Boni created is a blueprint for repositioning organizations and a model for any executive facing business dysfunctions and setbacks. The process is divided into three phases, each anchored with the easy to remember moniker the "ABCs to advance" : phase 1: hatch the plan; phase 2: kick off the plan; phase 3: execute the plan. This is a valuable guide for how to think in a crisis and how to cultivate the character traits to become an effective leader. --